(untitled) (MSW Management Journal, 2026)
Background The development of multi drug resistant microorganisms as well as the growing demand for biocompatibility of various medical materials has led pharmaceutical companies to focus on natural products. Punica granatum is recognized as a rich source of various bioactive compounds including tannins and flavonoids which possess substantial therapeutic value. Aim The purpose of the present study was to investigate the antimicrobial properties of Punica granatum ethanolic extract as a potential candidate for biomedical applications. Materials and Methods An 80 percent ethanol extract was prepared from dehydrated Punica granatum. Antimicrobial activities against Staphylococcus aureus and Candida albicans were evaluated using the disk diffusion method at concentrations of 25 50 and 100 mg mL. Hemocompatibility tests based on ASTM F756 00 involved determining the hemolytic percentage of the extract when exposed to blood samples. Results The antimicrobial activities of the extract were highly promising. In the case of Staphylococcus aureus the maximum zone of inhibition ZOI was 25 mm at 25 mg mL. In the case of Candida albicans a very significant zone of inhibition of 35 mm was observed at the same concentration. In the hemocompatibility test the hemolysis percentage was less than 3 percent thus falling into the category of moderately hemolytic and within the permissible limit less than 5 percent for biomedical materials. Conclusion The ethanol extract of Punica granatum demonstrated strong antimicrobial activity along with good hemocompatibility. Therefore the ethanolic extract of Punica granatum could be used to develop infection resistant and biocompatible technologies and may serve as a safe natural alternative to antibiotics.